Danmarks Omsætning med Udlandet af Landbrugsprodukter i Kalenderaaret 1898. - Reck, Frederik (Tidsskrift for Landøkonomi, 2018)
Danmarks Omsætning med Udlandet af Landbrugsprodukter i Kalenderaaret 1898.